Faktor yang Mempengaruhi Ekuitas Merek dengan Kepercayaan sebagai Mediasi pada Industri Transportasi Online di JABODETABEK Indonesia - Wisnu Budi Prasetyo; Wit Azizah Syabany (JUDICIOUS, 2023)
Indonesia is also experiencing rapid technological progress. This can be seen from the advancement of technology that supports information. The existence of the internet marks the development of this technology. Social media is one of the advanced technologies used to disseminate information. E-WOM influences the brand so that consumers are more aware of the brand. The purpose of this research is to find out how personality, social, and social media information characteristics impact brand equity through e-WOM and trust, and to find out how trust and service quality impact brand equity. This research was conducted on 176 online transportation users in Jabodetabek using SEM analysis. The results show that features of social media use are positively correlated with brand equity, features of social media use are positively correlated with trust, e-WOM is not positively correlated with brand equity, e-WOM is positively correlated with trust, and trust is positively correlated with brand equity. The research suggestions are expected to help researchers and organizational development practitioners find the effect of social characteristics, personality, and information on social media use on equity through e-WOM and trust.